The Role Of A Semi-sports Games In Reducing Child - Ben Hadj Tahar, Abdelkader; Bensaid, Mohammed El Amin; Boudebza, Mostafa (جامعة الوادي - University of Eloued, 2022)
. الملخص: تهدف هذه الدراسة الى التعرف على دور برنامج ألعاب شبه رياضية في الحد من فرط حركة الأطفال خلال فترة الحجر المنزلي لفيروس كوفيد 19 من وجهة نظر الأولياء، ولتحقيق اهداف الدراسة تم الاعتماد على المنهج التجريبي، حيث تم ارسال المقياس على اولياء عينة الدراسة المكونة من (12) تلميذا من ذوي اضطراب فرط الحركة السنة الثانية ابتدائي، وبعد المعالجة الاحصائية توصلت الدراسة الى وجود فروق ذات دلالة احصائية بين القياس القبلي والبعدي على مقياس كونز لفرط الحركة لصالح القياس البعدي،.Abstract: this study aims to identify the effect of semi-sport games program in reducing hyperactivity in children during confinement due to covid-19 from the parents perspective and to achieve the objective of the study the Experimental method was used, where the scale was sent to parents of the sample(12) students of second year primary school with hyperactivity disorder, After statistical processing the study concluded that there are statistically significant differences between pre-measurement and post-measurement on the scale conners for hyperactivity in favor of postmeasurement.
Hyperactivity During The Home Quarantine Period Of Covid-19
مقال
Keywords: الألعاب الشبه ریاضیة؛ اضطراب فرط الحركة؛ الحجر المنزلي؛ فیروس كوفید1; semi-sport games; hyperactivity disorder; Home quarantine; Covid-19